Trazabilidad microbiológica en sitios poco monitoreados y contaminados con arsénico proveniente de fuentes naturales entre los 3500 y 3600 m.s.n.m. en la parroquia de Toacaso. - Caceres Zumbay, Jenifer Elizabeth (2022)
Arsenic-contaminated water when used as a source of irrigation and human consumption, it generates diseases such as cancer, skin eczema, leukemia, and damage to the neurological system, among others. The parish of Toacaso, located in the province of Cotopaxi, has arsenic contamination in its water, which comes naturally from the Iliniza snow-capped mountain, a resource that, when used in agriculture, has caused the accumulation of this metalloid in crops. Due to this problem, the present research was carried out in two phases: field and laboratory, since the established objectives are: 1) To carry out the biophysical characterization of the study area at an altitude of 3500 - 3600 m.a.s.l., through the delimitation and cutting of the study area, which will be processed with the Geographic Information System software (Qgis 2.18) attachment to secondary or bibliographic information; 2) Determine the concentration of arsenic and water quality present in the water resource in the ‘Quebrada Talahuachana’, through analyses carried out in two seasons (rainy and dry) through the National Laboratory of Water and Sediment Quality (LANCAS) whose results of the analyzed parameters such as pH, Arsenic, Manganese, Sulfates, Dissolved Oxygen and Fecal Coliforms will be compared with the TULSMA 2017 and INEN 1108: 2020 regulations for irrigation and human consumption use; 3) Identify the microbiological traceability present in the study area, performing sampling, seeding, isolation and microbial observation of water samples in the laboratory of the Technical University of Cotopaxi (CAREN). The results of this research determined that the conditions of volcanic formation, slopes, and its annual rainfall of 1272 (mm) are the factors that cause the presence of geogenic arsenic in its water resources. In addition, the results issued establish that according to the TULSMA regulations the water quality is suitable for irrigation, However, it did not occur within the INEN standards because the concentration of arsenic exceeds the LMP for human consumption. Finally, in the isolation of bacterial assemblages, the presence of bacteria whose fermentation belongs to positive (+) and negative (-) lactose was obtained, which could help degrade arsenic, either through its metabolization or detoxification in an efficient and ecological way.